Human capital constraints in South Africa - Kleynhans, Ewert P. J. (Managing global transitions, 2012)
This paper examines human capital constraints in the South African economy, and the austerity of these constraints on firms in the country. The two key human capital constraints explored in this article are the inadequately educated workforce and labour market distortions. Regression analysis was applied to examine determinants of increased labour productivity in manufacturing firms. Education and labour market distortions were found to have a varying influence on output per worker. Principal Component Analysis (pca) of the explanatory variables achieved similar results. This study found that the highest percentage of the total variance is explained by latent variables that incorporate education, training, compensation, region and Sector Education Training Authority (seta) support and effectiveness.
Keywords: constraints; delo; education; efficiency; human capital; izobraževanje; Južna Afrika; labour; manufacturing; omejitve; productivity; proizvodnja; South Africa; storilnost; učinkovitost; zaposleni